Synchronized acoustic emission and gait analysis of total hip replacement patients. (April 2022) - FitzPatrick, A.J.; Rodgers, G.W.; Fernandez, J.W.; Hooper, G.J.
Abstract: Objective: Increased numbers of joint replacement patients suffering implant wear and/or loosening has created a need for development of non-invasive early diagnosis techniques. Acoustic emission monitoring has shown diagnostic potential for joint replacements, but has not previously been linked to temporal stages of the gait cycle, biomechanical modelling, and hip flexion angles. This combination of acoustic and biomechanics parameters is the novel contribution of this manuscript. Methods: Total hip replacement acoustic emissions are synchronized with gait data using three-dimensional video motion capture from total hip replacement patients. Hip joint motions are estimated from the motion data, using OpenSim musculoskeletal modelling software, synchronized in time with the recorded acoustic emission data. Results: Substantial acoustic emissions have been observed occurring only during the stance phase of the gait cycle in two of three patients. Repeated audible squeaking was observed from one patient during terminal stance. Squeaking was observed to occur from approximately 5°-15° hip extension when high joint loading and rapid changes in hip angle were occurring. These are also the likely conditions of the largest implant bearing surface wear rates. Conclusion: Specific regions within the gait cycle that peak acoustic emission signals occur are identified, providing insight into underlying biomechanics. High implant load and high angular velocity during the stance phase are correlated with peak acoustic emissions. Significance: This is one of the first studies to relate recorded in-vivo human implant acoustic emissions with lower-limb biomechanical modelling, providing new insight into in-vivo total hip replacement implant mechanics. Further research is needed to increase patient numbers and verify if these results apply more broadly to a wider cohort.